2006
DOI: 10.1128/jvi.00256-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Permissive Epitope Insertion Site in Adenovirus Hexon

Abstract: A robust immune response is generated against components of the adenovirus capsid. In particular, a potent and long-lived humoral response is elicited against the hexon protein. This is due to the efficient presentation of adenovirus capsid proteins to CD4 ؉ T cells by antigen-presenting cells, in addition to the highly repetitive structure of the adenovirus capsids, which can efficiently stimulate B-cell proliferation. In the present study, we take advantage of this immune response by inserting epitopes again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 80 publications
1
54
2
Order By: Relevance
“…It has also been possible to incorporate immunogenic epitopes into permissive sites of hexon, a major capsid protein, and the resulting vaccines exhibit robust protective efficacy (Worgall et al, 2005(Worgall et al, , 2007. However, the addition of foreign immunogens into hexon is limited by size; insertions of only up to 53 amino acids in the hypervariable region 5 of hexon are tolerated for viable virus recovery (McConnell et al, 2006;Matthews et al, 2008). In contrast, studies on the minor capsid protein, pIX, have indicated that up to 1000 kDa can be fused to the C terminus of the protein, allowing surface exposure of the foreign protein without substantial impact on the formation of virions (Dmitriev et al, 2002;Campos et al, 2004;Meulenbroek et al, 2004;Le et al, 2005;Li et al, 2005;Matthews et al, 2006;Vellinga et al, 2007).…”
Section: Adenovirus-based Vaccine Vectorsmentioning
confidence: 99%
“…It has also been possible to incorporate immunogenic epitopes into permissive sites of hexon, a major capsid protein, and the resulting vaccines exhibit robust protective efficacy (Worgall et al, 2005(Worgall et al, , 2007. However, the addition of foreign immunogens into hexon is limited by size; insertions of only up to 53 amino acids in the hypervariable region 5 of hexon are tolerated for viable virus recovery (McConnell et al, 2006;Matthews et al, 2008). In contrast, studies on the minor capsid protein, pIX, have indicated that up to 1000 kDa can be fused to the C terminus of the protein, allowing surface exposure of the foreign protein without substantial impact on the formation of virions (Dmitriev et al, 2002;Campos et al, 2004;Meulenbroek et al, 2004;Le et al, 2005;Li et al, 2005;Matthews et al, 2006;Vellinga et al, 2007).…”
Section: Adenovirus-based Vaccine Vectorsmentioning
confidence: 99%
“…For the presentation of the vaccine antigen we chose the pIX protein, because in contrast to hexon, fiber, and penton base, which have been used before for the display of single epitopes (5,22,25,26,43), pIX allows the incorporation of large proteins without loss of function and virion integrity (24,28). Incorporation of a whole protein is an interesting option, as the presence of multiple relevant epitopes in the vaccine allows the induction of a broader and more diverse immune response.…”
Section: Fig 7 F-mulv Env-specific Cd4mentioning
confidence: 99%
“…These were mostly inserted into external loops of the hexon protein (5,22,25,26,43), which is the main component of the adenovirus capsid, but also other components of the capsid, such as fiber, protein IX, and penton base, have been evaluated (22). These studies showed that incorporation of single epitopes into capsid proteins of adenovirus leads to induction of antibody and CD4 ϩ T-cell responses, suggesting that incorporation of epitopes into the adenovirus capsid is a useful tool for epitope-based vaccination.…”
mentioning
confidence: 99%
“…The open reading frame encoding the 22-kDa protein was amplified using primers 22kDafor (5Ј-ACCCATGGCACCCAAAAAGAA GC-3Ј) and 22kDarev (5Ј-TTCTCGAGTCCGGTCGCCTTTGCTTC-3Ј) from the previously created cAd212 cosmid (22). The resulting PCR product was inserted into the pCR II-Blunt-TOPO vector (Invitrogen) according to the manufacturer's protocol to create pCRBT-L422kDa.…”
Section: Plasmid Constructionmentioning
confidence: 99%